Estudio Comparativo De Las Metodologías De Análisis Forense Informático Para La Examinación De Datos En Medios Digitales - Iván Mesias Hidalgo Cajo; Saul Yasaca Pucuna; Byron Geovanny Hidalgo Cajo; Víctor Manuel Oquendo Coronado; Fanny Valeria Salazar Orozco (European Scientific Journal, ESJ, 2018)
The aim of this research is to compare the different standards and methodologies of computer forensic analysis used in the examination of data in digital media. The research was developed based on the scientific method, and a standard and two analysis methodologies were specifically used, which were applied to ten researchers. The analysis variables were based on the feasibility of use and on the time of extracting information from the computer. Among the comparison results of the different methodologies analyzed, it was determined that for the Methodology UNE 71506: 2013, 60% of the researchers used it due to the feasibility of use because it is made up of a robust process (contains the most detailed steps of computer forensics). Reliable and applicable in any field necessarily supervised by specialists working in the area, compared to the National Institute of Standards and Technology that selected 30%, Integrated Digital Investigation Process 10%. Regarding the time of analysis in the examination of digital media with different methodologies (Case study: Extraction of a file of 100 Mb, of a hard disk of 20 Gb in off mode. It is revealed that in the UNE 71506: 2013 it took less than 1 hour compared to the National Institute of Standards and Technology, which took between 1 and less than 2 hours, the Integrated Digital Investigation Process, which lasted longer than 3 hours. In addition, with the use of the Methodology UNE 71506: 2013, it was possible to have greater feasibility in the examination of digital media, since it is composed of four stages such as the preservation, acquisition, analysis and presentation of information results.